Antiretroviral therapy uptake, attrition, adherence and outcomes among HIV-infected female sex workers: a systematic review and meta-analysis. - Elisa Mountain; Sharmistha Mishra; Peter Vickerman; Michael Pickles; Charles Gilks; Marie-Claude Boily (PLoS ONE)
Purpose We aimed to characterize the antiretroviral therapy (ART) cascade among female sex workers (FSWs) globally. Methods We systematically searched PubMed, Embase and MEDLINE in March 2014 to identify studies reporting on ART uptake, attrition, adherence, and outcomes (viral suppression or CD4 count improvements) among HIV-infected FSWs globally. When possible, available estimates were pooled using random effects meta-analyses (with heterogeneity assessed using Cochran's Q test and I2 statistic). Results 39 studies, reporting on 21 different FSW study populations in Asia, Africa, North America, South America, and Central America and the Caribbean, were included. Current ART use among HIV-infected FSWs was 38% (95% CI: 29%-48%, I2 = 96%, 15 studies), and estimates were similar between high-, and low- and middle-income countries. Ever ART use among HIV-infected FSWs was greater in high-income countries (80%; 95% CI: 48%-94%, I2 = 70%, 2 studies) compared to low- and middle-income countries (36%; 95% CI: 7%-81%, I2 = 99%, 3 studies). Loss to follow-up after ART initiation was 6% (95% CI: 3%-11%, I2 = 0%, 3 studies) and death after ART initiation was 6% (95% CI: 3%-11%, I2 = 0%, 3 studies). The fraction adherent to ≥95% of prescribed pills was 76% (95% CI: 68%-83%, I2 = 36%, 4 studies), and 57% (95% CI: 46%-68%, I2 = 82%, 4 studies) of FSWs on ART were virally suppressed. Median gains in CD4 count after 6 to 36 months on ART, ranged between 103 and 241 cells/mm3 (4 studies). Conclusions Despite global increases in ART coverage, there is a concerning lack of published data on HIV treatment for FSWs. Available data suggest that FSWs can achieve levels of ART uptake, retention, adherence, and treatment response comparable to that seen among women in the general population, but these data are from only a few research settings. More routine programme data on HIV treatment among FSWs across settings should be collected and disseminated.